Simplifying
1.3(c + -4) = 2.6 + 0.7c
Reorder the terms:
1.3(-4 + c) = 2.6 + 0.7c
(-4 * 1.3 + c * 1.3) = 2.6 + 0.7c
(-5.2 + 1.3c) = 2.6 + 0.7c
Solving
-5.2 + 1.3c = 2.6 + 0.7c
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add '-0.7c' to each side of the equation.
-5.2 + 1.3c + -0.7c = 2.6 + 0.7c + -0.7c
Combine like terms: 1.3c + -0.7c = 0.6c
-5.2 + 0.6c = 2.6 + 0.7c + -0.7c
Combine like terms: 0.7c + -0.7c = 0.0
-5.2 + 0.6c = 2.6 + 0.0
-5.2 + 0.6c = 2.6
Add '5.2' to each side of the equation.
-5.2 + 5.2 + 0.6c = 2.6 + 5.2
Combine like terms: -5.2 + 5.2 = 0.0
0.0 + 0.6c = 2.6 + 5.2
0.6c = 2.6 + 5.2
Combine like terms: 2.6 + 5.2 = 7.8
0.6c = 7.8
Divide each side by '0.6'.
c = 13
Simplifying
c = 13